The combined effects of Polyethylene Terephthalate and rubber crumb as fine aggregate in concrete / Norhana Abdul Rahman - Abdul Rahman, Norhana; Kamaruddin, Kartini; Mohd Saman, Hamidah; Awang, Haryati (Universiti Teknologi Mara Cawangan Pulau Pinang, 2017)
Currently, the need to incorporate recycled materials such as plastics and rubbers as replacements to raw materials is becoming more important than ever before. In this study, the combined effects of Polyethylene Terephthalate (PET) and rubber crumb (RC) as fine aggregate replacement in concrete are investigated. This study evaluated the mechanical (compressive strength and flexural strength) and durability properties (electrical resistivity and water absorption) of the concrete. The fine aggregate was replaced at 10%, 20% and 30% by weight of binder and tested for 7, 28, 60 and 90 days of curing. The results showed that by increasing the replacement of PET in higher proportion (up to 20%) and RC (up to 10%) the compressive strength of concretes did decrease. The same trend followed for the flexural strength in which strength was reduced as the replacements level increased. The electrical resistivity increased with the increased of PET and RC replacement in concrete. Meanwhile, the water absorption of concretes increased with the increased of PET and RC replacement. Overall, the PET and rubber crumb can be utilized up to certain percentages in replacing fine aggregates in concrete.